APLIKASI MINIMASI BIAYA SEWA PADA PENJADWALAN FLOWSHOP BERBASIS ANDROID - Muhammad Faudzi Bahari; M. Adib Jauhari Dwi Putra; Achamd Ridwan; Taftazani Ghazi Pratama (Universitas Muhammadiyah Kudus, 2023)
4-D (Define, Design, Develop and Disseminate) Method used in this research. This research has made an android based application. The application that has been made is the development of mathematical theories that have been found by previous researchers. The Application that has been made can solve minimize rental cost on flowshop scheduling problem. This study uses simulations to conduct trials on applications that have been made. This Application is expected to make industrial revolution era 4.0’s dreams come true.